2010
DOI: 10.2135/cropsci2009.03.0131
|View full text |Cite
|
Sign up to set email alerts
|

Cool‐Season Turfgrass Colony and Seed Survival in a Restored Prairie

Abstract: Nonnative cool‐season turfgrasses are sometimes considered to be invasive species in restored prairies. The method of their invasiveness is poorly understood, as in many cases prairie restoration projects occur where the grasses were formerly planted. Colonies of 10 turfgrass species were placed into two anthropogenic prairies and monitored over a 2‐yr period. Colonies of most species, including Kentucky bluegrass (Poa pratensis L.), creeping bentgrass (Agrostis stolonifera L.), and tall fescue [Schedonorus ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The lawns we studied had similar communities to temperate semi-natural grasslands. Like in other studies (Richmond, Grewal, & Cardina, 2006;Garrison and Stier, 2010), the observed patterns in plant cover and density mainly reflected establishment and growth characteristics of the grass species planted. The most abundant species we observed, i.e.…”
Section: Lawn Characteristicssupporting
confidence: 71%
“…The lawns we studied had similar communities to temperate semi-natural grasslands. Like in other studies (Richmond, Grewal, & Cardina, 2006;Garrison and Stier, 2010), the observed patterns in plant cover and density mainly reflected establishment and growth characteristics of the grass species planted. The most abundant species we observed, i.e.…”
Section: Lawn Characteristicssupporting
confidence: 71%
“…The ability of turfgrasses to be outcompeted may depend on the surrounding species and other factors. Vegetative plugs of 10 C 3 turfgrass species failed to thrive when placed in two prairie ecosystems due to herbivory, environmental stress, and competition from the larger prairie plants (Garrison and Stier, 2010). Surveys of natural areas surrounding 12 largely rural golf courses ranging in age from 4 to 112 yr showed a relative lack of turfgrass ingress (Garrison, 2009).…”
Section: Invasive Speciesmentioning
confidence: 99%
“…The Wisconsin location was a dormant seeding, and lack of moisture during 2005 seemed to affect growth more than any potential winter injury. Seed that did not germinate in spring 2005 would have been unlikely to survive until more favorable conditions arose (7). In North Dakota, the trial was seeded in the early fall, and first year quality was inadequate (4.7), which may have been caused by stand loss caused by the death of young tall fescue plants during the winter of 2005-2006.…”
Section: Best Options For Mowed Low-input Turf Areasmentioning
confidence: 99%